Revised History and New Identity in East Europe: Ревидирана историја и нов идентитет во Источна Европа - Kuljić, Todor; Bužarovska, Rumena (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Todor Kuljić | Тодор Куљиќ Title (English): Revised History and New Identity in East Europe Title (Macedonian): Ревидирана историја и нов идентитет во Источна Европа Translated by (English to Macedonian): Rumena Bužarovska | Румена Бужаровска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 63-86 Page Count: 23 Citation (English): Todor Kuljić, “Revised History and New Identity in East Europe,” Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 63-86. Citation (Macedonian): Тодор Куљиќ, „Ревидирана историја и нов идентитет во Источна Европа“, превод од англиски Румена Бужаровска, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 63-86.